Blueprint for Sustainable Living - European Investment Bank (European Investment Bank, 2024)
A blueprint presents drawings, dimensions and notes. This report draws vivid pictures of the beneficiaries of European Investment Bank projects in 2023. It includes data on the dimensions of our massive overall investment and the importance of our loans to each of our beneficiaries during the year. It notes the EU policies and expertise that lead us to make each of our investments.